Comparative Assessment of the Efficacy of Commercial Hand Sanitizers Against Human Norovirus Evaluated by an in vivo Fingerpad Method - Escudero-Abarca, Blanca I.; Goulter, Rebecca M.; Manuel, Clyde S.; Leslie, Rachel A.; Green, Kristen; Arbogast, James W.; Jaykus, Lee-Ann (Frontiers in Microbiology, 2022)
Human noroviruses (hNoV) are the leading cause of acute non-bacterial gastroenteritis worldwide and contaminated hands play a significant role in the spread of disease. Some hand sanitizers claim to interrupt hNoV transmission, but their antiviral efficacy on human hands is poorly characterized. The purpose of this work was to characterize the efficacy of representative commercial hand sanitizers against hNoV using an in vivo fingerpad method (ASTM E1838-17). Eight products (seven ethanol-based and one benzalkonium chloride [BAK]-based), and a benchmark 60% ethanol solution, were each evaluated on ten human volunteers using the epidemic GII.4 hNoV strain. Virus titers before and after treatment were evaluated by RT-qPCR preceded by RNase treatment; product efficacy was characterized by log10 reduction (LR) in hNoV genome equivalent copies after treatment. The benchmark treatment produced a 1.7±0.5 LR, compared with Product A (containing 85% ethanol) which produced a 3.3±0.3 LR and was the most efficacious (p<0.05). Product B (containing 70% ethanol), while less efficacious than Product A (p<0.05), performed better than the benchmark with a LR of 2.4±0.4. Five of the other ethanol-based products (labeled ethanol concentration ranges of 62-80%) showed similar efficacy to the 60% ethanol benchmark with LR ranging from 1.3 to 2.0 (p>0.05). Product H (0.1% BAK) was less effective than the benchmark with a LR of 0.30.2 (p<0.05). None of the products screened were able to completely eliminate hNoV (maximum assay resolution 5.0 LR). Product performance was variable and appears driven by overall formulation. There remains a need for more hand sanitizer formulations having greater activity against hNoV, a virus that is comparatively recalcitrant relative to other pathogens of concern in community, healthcare, and food preparation environments.